Ways of Seeing in the Neoliberal State - Grønstad, Asbjørn Skarsvåg. author. aut Link
IX, 116 p. 1 illus.
Keywords: This book focuses on the theme of counter-surveillance in art through a multi-faceted engagement with the highly controversial Norwegian play Ways of Seeing. Denounced by the prime minister and subject to a police investigation, the play gained notoriety when it featured footage showing the homes of the country’s financial and political elite as part of its scenography. The book provides a thorough consideration of the work’s reception context before elucidating its relation to the politics of neoliberalism. What is foregrounded in this analysis are, first, the use of an aesthetics of sousveillance to visualize the material infrastructure of racism and right-wing populism, second, the tangled interrelations of art and law, third, questions of censorship and artistic freedom, and fourth, the promotion of an alternative mode of political governance – grounded in feminism and ecological awareness – through the example of the Rojava experiment. Asbjørn Skarsvåg Grønstad is a film scholar and professor of Visual Culture in the Department of Information Science and Media Studies, University of Bergen, Norway. He is founding director of the Nomadikon Center for Visual Culture and the author/editor of eleven books, the most recent of which are the co-edited collection Gestures of Seeing in Film, Video and Drawing (2016), Film and the Ethical Imagination (2016), Invisibility in Visual and Material Culture (co-edited with Øyvind Vågnes, 2019), and Rethinking Art and Visual Culture: The Poetics of Opacity (2020). Grønstad is also a founding editor of the peer-reviewed journal Ekphrasis: Nordic Journal of Visual Culture.